Incremental test design, peak `aerobic` running speed and endurance performance in runners - Machado, F. A.; Kravchychyn, A. C. P.; Peserico, C. S.; da Silva, D. F.; Mezzaroba, P. V. (Journal of Science and Medicine in Sport, 2013)
Objectives: Peak running speed obtained during an incremental treadmill test (Vpeak) is a good predictor of endurance run performance. However, the best-designed protocol for Vpeak determination and the best Vpeak definition remain unknown. Therefore, this study examined the influence of stage duration and Vpeak definition on the relationship between Vpeak and endurance run performance. Design: Relationship. Methods: Twenty-seven male, recreational, endurance-trained runners (10-km running pace: 10-17 km h-1) performed, in counterbalanced order, three continuous incremental treadmill tests of different stage durations (1-, 2-, or 3-min) to determine Vpeak, and two 5-km and two 10-km time trials on a 400-m track to obtain their 5-km and 10-km run performances. Vpeak was defined as either (a) the highest speed that could be maintained for a complete minute (Vpeak-60 s), (b) the speed of the last complete stage (Vpeak-C), or (c) the speed of the last complete stage added to the multiplication of the speed increment by the completed fraction of the incomplete stage (Vpeak-P). Results: The Vpeak determined during the 3-min stage duration protocol was the most highly correlated with both the 5-km (r = 0.95) and 10-km (r = 0.92) running performances and these relationships were minimally influenced by the Vpeak definition. However, independent of the stage duration, the Vpeak-P provided the highest correlation with both running performances. Conclusions: Incremental treadmill tests comprising 3-min stage duration is preferred to 1-min and 2-min stage duration protocols in order to determine Vpeak to accurately predict 5-km and 10-km running performances. Further, Vpeak-P should be used as standard for the determination of Vpeak.